Size and structure of hexanuclear plutonium oxo‐hydroxo clusters in aqueous solution from synchrotron analysis. (15th December 2021) - Dumas, Thomas; Virot, Matthieu; Menut, Denis; Tamain, Christelle; Micheau, Cyril; Dourdain, Sandrine; Diat, Olivier
Abstract : A water‐soluble plutonium cluster made of six plutonium atoms decorated by four 1, 4, 7, 10‐tetraazacyclododecane‐1, 4, 7, 10‐tetraacetic acid ligands is characterized by small‐angle X‐ray scattering (SAXS) and extended X‐ray absorption fine structure (EXAFS). Abstract : The size and shape of a water‐soluble hexanuclear plutonium cluster were probed by combining synchrotron small‐angle X‐ray scattering (SAXS) and extended X‐ray absorption fine structure (EXAFS). A specific setup coupling both techniques and dedicated to radioactive samples on the MARS beamline endstation at Synchrotron SOLEIL is described. The plutonium hexanuclear cores are well stabilized by the 1, 4, 7, 10‐tetraazacyclododecane‐1, 4, 7, 10‐tetraacetic acid ligands and this allows a good evaluation of the setup to probe the very small plutonium core. The results show that, in spite of the constrained conditions required to avoid any risk of sample dispersion, the flux and the sample environment are optimized to obtain a very good signal‐to‐noise ratio, allowing the detection of small plutonium aggregates in an aqueous phase. The structure of the well defined hexanuclear cluster has been confirmed by EXAFS measurements in solution and correlated with SAXS data processing and modelling. An iterative comparison of classical fit models (Guinier or sphere form factor) with the experimental results allowed a better interpretation of the SAXS signal that will be relevant for future work under environmentally relevant conditions.